The EU-CAN dialogue: opportunities to consolidate Andean integration and its relations with the FTA with the USA - García Álvarez, Santiago (2016)
This article reviews the process of dialogue between the European Union and the Andean Community of Nations. It analyses whether the Andean countries could satisfy the European requirements for the signature of Association Agreements. According to the author, there are several political and institutional obstacles that inhibit the Andean countries to consolidate their space at the international arena. An association agreement with the European Union could foster cooperation actions aimed at strengthening social cohesion at the Andean Region.